(untitled) - Loizos, Andreas (London, 2007)
Recent developments and research on mechanistic pavement analysis, design and rehabilitation, their geotechnical aspects and the experimental determination ofmaterial model parameters. Ofinterest to those involved in computational simulation, experimental characterization and field testing for prediction of performance of various types of pavement.
Keywords: Pavements performance,Road materials,Kỹ nghệ đường bộ; Congresses,Congresses